Accounting and sustainable development: Reflections and propositions. (October 2017) - Bebbington, Jan; Russell, Shona; Thomson, Ian
Highlights: While social and environmental accounting scholarship has engaged with sustainable development more work remains to be done. A focus on accountability settings (rather than solely on accounting itself) will be needed so as to address sustainable development concerns. Explicit about theorising about engagement with practice is likely to advance social and environmental accounting scholarship. Abstract: This paper emerges from an invitation to reflect upon the achievements of social and environmental accounting as well as to identify the challenges that lie ahead as the field continues its engagement with the goal of sustainable development. Three perspectives are developed in pursuit of that aim, namely: exploring the nature of the issues and mode of academic inquiry that is 'fit for purpose' given the demands of sustainable development; considering if a de-centring of accounting and the embrace of more holistic versions of accountability would be productive for future scholarship; and an exploration of how we might conceptualise 'engagement' with practice in this context (and what is meant by practice and practitioner). Taken together, this paper seeks to provide points of provocation and encouragement to social and environmental accountants, critical accounting scholars and to those seeking to understand sustainable development scholarship and action.